Motorized pan-and-tilt camera head / Nor Azam Che Soh - Che Soh, Nor Azam (2019)
The purpose of this project is to design and develop a motorized pan-and-tilt camera head that can be remote controlled using a joystick with the aim to help cameraman control the camera from a distance and produce fluid motion. This is done by using LabVIEW software and MyRio as microcontroller. The design of the pan-and-tilt camera head equipped with two servo motors which are for panning and tilting respectively. The servo motors are supported by servo brackets. The choice of servo motor used directly affects the stability of the pan-and-tilt movement, therefore an analysis of the selection of servo motor was done to determine the suitable servo motor based on the camera used. It is observed from the datasheet that MG995 is suitable for the prototype of this project. The pan-and-tilt camera head was able to pan-and-tilt from 0° to 180° respectively. It can be remotely controlled using a joystick which is connected wirelessly. The pan-and-tilt was successfully implemented in a smooth manner.